2014
DOI: 10.1007/s12161-014-9795-9
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Tools Used to Distinguish Chemical Profiles of Plants Widely Consumed as Infusions and Dietary Supplements: Artichoke, Milk Thistle, and Borututu

Abstract: Artichoke, borututu and milk thistle are three medicinal plants widely consumed as infusions or included in dietary supplements (e.g., pills and syrups). Despite their high consumption, studies on nutritional value and primary metabolites are scarce, being only reported the composition in secondary metabolites such as phenolic compounds.Therefore, their nutritional value was assessed and analytical tools (liquid and gas chromatography coupled to different detectors) were used to distinguish the chemical profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
3
6
1
Order By: Relevance
“…In agreement with Pereira et al (2014a), in the present study the four vitamers of tocopherol were found in the borututu samples, with the prevalence of β-tocopherol (Table 2), but the highest total tocopherols content was obtained for the irradiated samples irradiated (both with 1 kGy and 10 kGy with 331.97 mg/100 g and 336.72 mg/100 g, respectively). With the exception of δ-tocopherol, the amount of the different isoforms was generally higher in the irradiated samples.…”
Section: Chemical Compositionsupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with Pereira et al (2014a), in the present study the four vitamers of tocopherol were found in the borututu samples, with the prevalence of β-tocopherol (Table 2), but the highest total tocopherols content was obtained for the irradiated samples irradiated (both with 1 kGy and 10 kGy with 331.97 mg/100 g and 336.72 mg/100 g, respectively). With the exception of δ-tocopherol, the amount of the different isoforms was generally higher in the irradiated samples.…”
Section: Chemical Compositionsupporting
confidence: 91%
“…With respect to organic acids (Table 3), it was possible to verify that the irradiation did not significantly affect these compounds in borututu samples, which showed the presence of oxalic, malic, shikimic, citric and fumaric acids in similar amounts, with higher oxalic, malic and citric acids content, similarly to what was observed in the previous work referred above (Pereira et al, 2014a). The preservation of organic acids is of great interest once they are related to plant foods organoleptic properties, namely their flavor, aromatic properties or consistence.…”
Section: Chemical Compositionsupporting
confidence: 84%
See 2 more Smart Citations
“…With the recent emergence of borututu bark as a new antioxidant herbal beverage and dietary supplement [1,6,18] and due to the scarcity of phytochemical investigation of this plant, the goal of this study was to utilize high-performance liquid chromatography (HPLC) and an activity-guided approach to determine the most active constituents of borututu bark in a 1,1-diphenyl-2-picrylhydrazyl (DPPH) free-radical scavenging assay. A qualitative HPLC method was developed for (i) fingerprinting borututu crude and commercial products; (ii) determining the major phytochemical markers of the bark; and (iii) verifying the purity of isolated compounds.…”
Section: Introductionmentioning
confidence: 99%